Simplified feeding strategies for the fed-batch cultivation of Kluyveromyces lactis GG799 for enhanced recombinant xylanase production - Md. Illias, Rosli (Springer Verlag, 2014)
A xylanase gene (xyn2) from Trichoderma reesei ATCC 58350 was previously cloned and expressed in Kluyveromyces lactis GG799. The production of the recombinant xylanase was conducted in a developed medium with an optimised batch and with fed-batches that were processed with glucose. The glucose served as a carbon source for cell growth and as an inducer for xylanase production. In a 1-L batch system, a glucose concentration of 20 g L-1 and 80 % dissolved oxygen were found to provide the best conditions for the tested ranges. A xylanase activity of 75.53 U mL-1 was obtained. However, in the batch mode, glucose depletions reduced the synthesis of recombinant xylanase by K. lactis GG799. To maximise the production of xylanase, further optimisation was performed using exponential feeding. We investigated the effects of various nitrogen sources combined with the carbon to nitrogen (C/N) molar ratio on the production of xylanase. Of the various nitrogen sources, yeast extract was found to be the most useful for recombinant xylanase production. The highest xylanase production (110.13 U mL-1) was measured at a C/N ratio of 50.08. These conditions led to a 45.8 % increase in xylanase activity compared with the batch cultures. Interestingly, the further addition of 500 g L-1 glucose led to a 6.2-fold increase (465.07 U mL-1) in recombinant xylanase activity. These findings, together with those of the exponential feeding strategy, indicate that the composition of the C/N molar ratio has a substantial impact on recombinant protein production in K. lactis.